Feasibility study of Replacing Currently used Freons with Ammonium Chloride and Barium Hydroxide for Freezing System - Rasaili, Prithivi; Bhattarai, Ajaya (Himalayan Journal of Science and Technology, 2023)
The machinery used to cool or freeze food uses a lot of energy. Consequently, it is necessary to lower energy use. Additionally, due to their significant global warming potential (GWP), traditional refrigerants must be replaced to help reduce greenhouse gas (GHG) emissions. Therefore, the usage of alternative refrigerants with lower GWPs is necessary. The possibility of the ammonium chloride (NH4Cl(s)) and solid hydrated barium hydroxide (Ba(OH)2.8H2O(s)) based non-freon refrigerant as a substitute refrigerant was evaluated in this study. Demo-tests were conducted using a prototype refrigerator, which is essentially a closed chamber with foam and PVC insulation. Despite reaching the freezing point satisfactorily, the stirring chamber of the prototype had an unpleasant ammonia odor. Due to the lack of equilibrium between the reactant and product, these components were not permanent solutions like freons. Therefore, further research is needed to determine how effective it would be as a refrigerant